STH – Secreting Pituitary Adenoma. Acromegaly Case without Successful Result - Akala Oluwatosin Shakirah (My University, 2017)
Clinical cases
Scientific advisers: assoc. prof. O. S. Makharynska, ass. prof. E. A. Golubkina, prof. M. I. Yabluchansky